Absence of a National Policy- ICT Incorporation in Uganda’s Higher Education Institutions - Jjagwe, George; Nanteza, Lucy Babirye (In Higher Education ICT Integration in Africa, 2025)
Uganda’s higher education (HE) system has massively expanded since its liberalization in 1993 (Saphina, 2017) with the introduction of neoliberal policies allowing both the private sector and the state to participate in its offering. This was aimed at providing more opportunities to Ugandans in different geographical locations to access higher education (Bisaso & Achanga, 2023). According to Uganda’s University and Other Tertiary Institutions Act 2001, the Ministry of Education is the overall coordinator and regulator of Uganda’s education. Below the ministry is the National Council for Higher Education (NCHE), a semi-autonomous body mandated to super vise all higher education institutions in Uganda. In the current setting, HE in Uganda includes universities; other degree awarding institutions (ODIs) such as Uganda Management Institute (UMI), which offers degrees up to the doctoral level; and other tertiary institutions (OTIs), such as Makerere Institute of Social Development (MISD), which are limited to only diploma pro grammes (Bisaso & Achanga, 2023). All these categories of HEIs include both public and private ones (Ministry of Education and Sports, 2019). According to NCHE’s State of Higher Education Report for 2020/2021, there were 246 HEs in Uganda (NCHE, 2023). Of these, 9 were public universities,1 48 were private universities, 19 were ODIs, and the rest (170) were OTIs. In terms of ownership as per the 2020/2021 NCHE report, the majority (74%) of the HEIs in Uganda were privately owned, leaving only 26% under public ownership. This signifies that most of the HEIs in Uganda are privately owned, operating with the goal of profits.
Keywords: ICT; National Policy; Higher Education Institutions